2016
DOI: 10.1155/2016/6906712
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Omega‐3 Polyunsaturated Fatty Acids in Stroke

Abstract: Stroke is the third commonest cause of death following cardiovascular diseases and cancer. In particular, in recent years, the morbidity and mortality of stroke keep remarkable growing. However, stroke still captures people attention far less than cardiovascular diseases and cancer. Past studies have shown that oxidative stress and inflammation play crucial roles in the progress of cerebral injury induced by stroke. Evidence is accumulating that the dietary supplementation of fish oil exhibits beneficial effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 85 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…In contrast, in the group without a tourniquet, there was no significant difference in the quadriceps muscle volume pre-and post-operatively [14]. Additionally, previous studies have shown that n-3 PUFA supplementation might attenuate IR-induced cell death in the brain, lung, intestine, and liver [17,[19][20][21]. Furthermore, a recent study in a mouse model of hind limb IR showed that fish oil (n-3 PUFA) pre-treatment suppressed muscle damage through modulating the inflammatory response [30].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, in the group without a tourniquet, there was no significant difference in the quadriceps muscle volume pre-and post-operatively [14]. Additionally, previous studies have shown that n-3 PUFA supplementation might attenuate IR-induced cell death in the brain, lung, intestine, and liver [17,[19][20][21]. Furthermore, a recent study in a mouse model of hind limb IR showed that fish oil (n-3 PUFA) pre-treatment suppressed muscle damage through modulating the inflammatory response [30].…”
Section: Discussionmentioning
confidence: 96%
“…IR injury has been shown to be preventable by nutritional preconditioning [17][18][19]. Studies have demonstrated that intake of sufficient amounts of dietary n-3 polyunsaturated fatty acids (PUFA), such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), can limit tissue damage associated with IR [17,18,20,21]. The suspected molecular mechanism underlying this phenomenon can be attributed to the anti-inflammatory and antioxidant properties of n-3 PUFA [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular exhaustion in turn leads to the development of several diseases, such as gastrointestinal ulcers, hyperglycemia, and hepatic dysfunction [27]. Thus, natural antioxidants provide cellular protection and lead to favorable effects in diabetes mellitus [28] and the majority of inflammatory and cardiovascular diseases [29]. Examples of naturally occurring antioxidants are flavonoids, phenolic acids, coumarin, isorhamnetin and quercetin that were separated and identified from P. angustifolia extract with promising anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases refer to a collective term for heart and/or blood vessels related diseases that are by far, the most leading cause of mortality worldwide with 17.9 million deaths reported in 2018 [13]. Therefore, the effects of n-3 PUFA on major CVD including coronary heart disease (CHD) and stroke have been reported in numerous studies [54,55,56]. One of the potential roles of n-3 PUFA in reducing the risk of CHD is by counteracting many steps of atherosclerosis [57], the major cause of CHD [58].…”
Section: Metabolic Pathways Human Health Benefits and Recommendedmentioning
confidence: 99%
“…In terms of stroke, dietary consumption of n-3 PUFA can reduce the volume of ischemic stroke [60] by promoting antioxidant enzyme activities or partly acting as an antioxidant. n-3 PUFA can provide further benefits relating to stroke post-treatments [55], by generating other important responses such as neuranagenesis and revascularization. The latest meta-analysis of prospective cohort studies [61] supported a strong inverse relationship between daily fish intake and the risk of stroke.…”
Section: Metabolic Pathways Human Health Benefits and Recommendedmentioning
confidence: 99%